Synergistic effects of AgNPs and zileuton on PCOS via ferroptosis and inflammation mitigation - Amira K. Eltokhy; Rehab Ahmed Ahmed El-shaer; Omnia Safwat El-Deeb; Eman E. Farghal; Rowida Raafat Ibrahim; Rasha Elesawy; Marwa Mahmoud Awad; Radwa Ismail; Shaimaa M. Motawea; Doaa Shatat; Yasser Mostafa Hafez; Hend Ahmed El hanafy; et al. (Redox Report, 2025)
Background: The most prevalent endocrine disorder affecting women is PCOS. Programmed death of ovarian cells has yet to be elucidated. Ferroptosis is a kind of iron-dependent necrosis featured by significantly Fe+2-dependent lipid peroxidation. The ongoing study aimed to reinforce fertility by combining therapy with AgNPs and (Zileuton) in PCOS rats’ model.Methods: The study included 75 adult female rats divided into 5 groups; control, PCOS, PCOS treated with AgNPs, PCOS treated with Zileuton, and PCOS group treated with AgNPs and Zileuton. The study investigated the anti-ferroptotic, anti-inflammatory, antioxidant, antiapoptotic, histopathological and immunohistochemical examinations of COX-2 and VEGF.Results: The combination of AgNPs and Zileuton showed significant reduction of inflammatory mediators (IL-6, TNF-α, NFk-B) compared with diseased group (P-value < 0.05), regression of ferroptosis marks (Panx1 and TLR4 expression, Fe+2 levels) compared with diseased group (P-value < 0.05), depression of apoptotic marker caspase 3 level compared with diseased animals (P-value < 0.05), depression of MDA level, elevation of HO-1, GPx4 activity, and reduction of Cox2 and VEGF as compared with the diseased, AgNPs or zileuton-treated groups (P-value < 0.05).Conclusion: The study showed that the combination of AgNPs and zileuton guards against, inflammation, apoptosis, and ferroptosis in PCO.